Single Stage Lateral Based Flap Urethroplasty and Two Stage Urethroplasty in Proximal Penile Hypospadias with Chordee : A Prospective Case Control Study - Biswas, Ipsita; Chakraborty, Abhi Kumar; Noor-ul Ferdous, Kazi Md.; Sultana, Hafiza (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Aims: Hypospadias is one of the commonest congenital abnormalities of the male genitalia. Proximal penile hypospadias is the challenging condition to correct. Lateral based flap (LB) procedure combines meatal based flap and pedicle flap technique into one procedure without the need for an intervening anastomosis. In this study we compared Lateral based flap (LB) procedure with conventional two stage urethroplasty for proximal penile hypospadias with chordee. The aim of this study was to find out the outcome of lateral based flap urethroplasty in treating proximal penile hypospadias with chordee over two stage procedure. Study Design: In this prospective study that carried out from 1st January 2012 to 30th June 2013, patients with proximal penile hypospadias from 6 months to 144 months (12yrs) of age attending at Dhaka Shishu (Children) Hospital out patient department were primarily enrolled for this study. Patients were grouped into A and B on the basis of repair by Lateral based flap single stage urethroplasty and by two stage techniques respectively. Results were evaluated after 6 months of urethroplasty and onward. Results: Total 24 Patients, ages ranged from 7 months to 10 years (mean 3.97 years) of proximal penile hypospadias (12patients in each group) were included. For Lateral based flap (LB) procedure (Group-A), mean time required for urethroplasty was 3.23 hours. On the other hand, for control group (Group-B) mean total time required was 3.99 hours (for orthoplasty 1.67 hours and for urethroplasty 2.32 hours). Urethrocutaneous fistula developed in 16.6% (2 patients) and glanular dehiscence in 8.3% (1 patient) in each group. In addition 25% (3 patients) in control group developed meatal stenosis. Satisfactory results were observed more than 83% of group-A patients and 58.3% of group B patients. Conclusions: The study reflects that lateral based flap (LB) procedure technique may offer the patients with proximal and severe forms of hypospadias, a good chance of a single stage operation with high success rate. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21018